2015
DOI: 10.1080/13811118.2015.1004473
|View full text |Cite
|
Sign up to set email alerts
|

Postcards in Persia: A Twelve to Twenty-four Month Follow-up of a Randomized Controlled Trial for Hospital-Treated Deliberate Self-Poisoning

Abstract: This study reports the outcomes, during follow-up, of a low-cost postcard intervention in a Randomized Control Trial of hospital-treated self-poisoning (n = 2300). The intervention was 9 postcards over 12 months (plus usual treatment) versus usual treatment. Three binary endpoints at 12-24 months (n = 2001) were: any suicidal ideation, suicide attempt, or self-cutting. There was a significant reduction in any suicidal ideation (RRR 0.20 CI 95% 0.13-0.27), (NNT 8, 6-13), and any suicide attempt (RRR 0.31, 0.06-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…The most common veteran recommendation for the frequency and duration of the intervention was monthly contacts for a period of a year. This generally matches several of the more common models in the literature that have sent 8–12 messages over the period of a year (Carter, Clover, Whyte, Dawson, & Deste, , ; Carter et al., ; Comtois et al., ; Hassanian‐Moghaddam et al., , ; Kapur et al., ; Robinson et al., ). Results on the importance of handwritten messages also generally supported existing models; clinical trials have not prioritized the use of handwritten messages, although some have included hand signatures or brief written components of the message (Reger et al., ; Robinson et al., , ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The most common veteran recommendation for the frequency and duration of the intervention was monthly contacts for a period of a year. This generally matches several of the more common models in the literature that have sent 8–12 messages over the period of a year (Carter, Clover, Whyte, Dawson, & Deste, , ; Carter et al., ; Comtois et al., ; Hassanian‐Moghaddam et al., , ; Kapur et al., ; Robinson et al., ). Results on the importance of handwritten messages also generally supported existing models; clinical trials have not prioritized the use of handwritten messages, although some have included hand signatures or brief written components of the message (Reger et al., ; Robinson et al., , ).…”
Section: Discussionsupporting
confidence: 81%
“…The clinical trials that have been completed were conducted with extremely variable methods (Reger et al., ). Contact has occurred through a variety of modalities in the trials, including letters (Motto, ; Motto & Bostrom, ), postcards (Carter, Clover, Whyte, Dawson, & Este, ), greeting cards (Hassanian‐Moghaddam, Sarjami, Kolahi, & Carter, ; Hassanian‐Moghaddam, Sarjami, Kolahi, Lewin, & Carter, ), e‐mail (Luxton et al., ), and text messages (Comtois, Kerbrat, Holman, & Muzychka, ). They have been sent by very different staff, ranging from treating psychiatrists and toxicologists to nonclinical staff who had contact with the patient in a clinic (Reger et al., ).…”
mentioning
confidence: 99%
“…The single largest trial of this intervention appeared to show a noticeably beneficial effect of postcards. 5,48 This is particularly interesting as more limited psychiatric resources would probably have been available in the control condition (TAU) in the Islamic Republic of Iran, where this study was conducted, as compared to Australia, New Zealand, and the UK, all of which have better resourced services. This raises the possibility that such an intervention may be more useful in such settings, although further trials in countries with poorly resourced psychiatric services are desirable to determine generalisability of the findings from the Iranian study.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…No data on changes in depression, hopelessness, or problem-solving were reported for any of the included trials. Dichotomous data on the number of participants self-reporting an episode of suicidal ideation were available for one trial, 45 48 …”
Section: (Insert Figure 7 About Here) (Insert Figure 8 About Here)mentioning
confidence: 99%
“…154 The findings were sustained at 24 months, with an 80% reduced risk of suicidal ideation (P<0.001) and 69% reduced risk of suicide attempt compared with controls (P=0.02). 155 Another RCT showed that among people who initially refused psychiatric follow-up, those who received letters regularly over five years had lower suicide rates than those who did not (3.9% v 4.6%), although the difference was significant only during the first two years directed at depression did not reduce suicidal ideation compared with usual treatment. 139 This raises an interesting question of whether psychotherapy directed towards the underlying mental disorder is sufficient to reduce suicidal ideation in the individual.…”
Section: Electroconvulsive Therapy (Ect)mentioning
confidence: 99%